Predicting post-surgical recurrent diabetic maculopathy in patients with type 2 diabetes mellitus (Ukrainian Journal of Ophthalmology, 2025)
Background: A closed subtotal vitrectomy (CSV), either alone or in combinations with internal limiting membrane (ILM) peeling, panretinal laser coagulation (PRLC); and cataract phacoemulsification (phaco) is a common treatment for diabetic maculopathy (DMP). Predicting post-surgical recurrent DMP in patients with type 2 diabetes mellitus (T2DM) based on identified pathogenetic factors for T2DM, and genotyping, medical history and clinical findings is a challenge.Purpose: To develop a model for predicting post-surgical recurrent DMP in patients with T2DM.Material and Methods: The study included 313 patients with T2DM (313 eyes) and DMP. Patients received one of the four types of surgical treatment: only a 25+ three-port CSTV (n=78); CSTV combined ILM peeling in a 2.5 mm- to 3.5-mm diameter macular area (n=85); CSTV combined with ILM peeling and panretinal laser coagulation (PRLC) (n=81); or CSTV combined with ILM peeling, PRLC and phaco (n=69). Preoperatively, ELISA was used to determine blood endothelin-1 (ET1) and tumor necrosis factor alpha (TNF?), and platelet-derived growth factor (PDGF-BB) levels, and polymorphisms of PDGFB (rs1800818) and TNF? (rs1800629) were investigated by real-time polymerase chain reaction. Follow-up visits were at months 1, 3, 6 and 12 after surgery. Multivariate logistic regression analysis was used to develop a model in Statistica 10 (GLZ; StatSoft, Tulsa, OK, USA).Results: The regression analysis showed no association of age, gender, severity and duration of T2DM, glucose and glycated hemoglobin (НbA1c) levels, diabetic retinopathy (DR) stage and severity on the ETDRS scale, central retinal thickness (CRT0), or blood ЕТ1 level with post-surgical recurrent DMP within 12 months after surgery. Genotypes of TNF-? (rs1800629) and PDGFB (rs1800629) polymorphisms, and blood PDGF-BB and TNF? levels were found to be significant predictors of the presence or absence of recurrent DMP. The probability of developing recurrent DMP was directly related to the TNF? rs1800629 polymorphism and blood PDGF-BB and TNF? levels, and inversely related to the PDGFB rs1800818 polymorphism. The percentage contributions of selected independent variables in predicting the dependent variable were found to be as follows: TNF? rs1800629, 90.25%; PDGFB rs1800818, 9.57%; PDGF-BB, 0.15%; and TNF?, 0.03%. Performance measures of the model were satisfactory, with Area under Curve (AUC) = 0.993; -2*log (Likelihood) = 197.80; ?2 = 110.15 (p < 0.001).Conclusion: TNF-? (rs1800629) and PDGFB (rs1800629) polymorphisms, and blood PDGF-BB and TNF? levels were predicting factors for recurrent DMP within 12 months after surgery.
Keywords: diabetic maculopathy; type 2 diabetes mellitus; surgical treatment; recurrence; rs180062; rs1800818; PDGF-BB; TNFα